Factors influencing age of common allergen introduction in early childhood - Marget, Michael; Virkud, Yamini V.; Shreffler, Wayne G.; Martin, Victoria M.; Yuan, Qian (Frontiers in Pediatrics, 2023)
Objectives: We evaluated factors influencing the timing of allergen introduction in the U.S., including updated peanut introduction guidelines. Study Design: The Gastrointestinal Microbiome and Allergic Proctocolitis (GMAP) study is a prospective observational cohort in suburban Massachusetts. Infants’ caregivers enrolled between 2014 and 2017, and they reported when they introduced common allergens to their child. Multivariable linear and survival regression analyses were used to examine factors influencing time of introduction of allergens. Results: By 9 months, children old enough to be potentially affected by NIAID’s 2017 peanut introduction guidelines were more often introduced to peanut than children enrolled well before guidelines publication (54% vs. 42%, OR: 1.63, CI: [1.03, 2.57], P = 0.03). At any given time, Black children were 73% (HR: 0.27, CI: [0.11, 0.69], P = 0.006) less likely to be introduced to peanut as early as White children. Asian children were, respectively, 36% (HR: 0.64, CI: [0.47, 0.86], P = 0.003) and 26% (HR: 0.74, CI: [0.55, 0.97], P = 0.03) less likely to be introduced to peanut and egg as early as White children. A first child was 27% (HR: 1.27, CI: [1.04, 1.56], P = 0.02) more likely to have been introduced to peanut earlier than a non-first child. There was no association between age of introduction and sex, gestational age, family history of food allergy, or other allergic comorbidities. Conclusion: Updated introduction guidelines, race, and birth order all influenced earlier introduction of peanut. Further studies to evaluate current practices for allergen introduction with a focus on potential disparities are needed.